DISTRIBUTION MODEL AND ACCRUED STIMULATING ALLOWANCES IN A MEDICAL ORGANIZATION WITH A HEALTH CENTER IN ITS STRUCTURE - T. M. Maksikova (Scientific Сentre for Family Health and Human Reproduction Problems, 2012)
This publication contains the universal model of the distribution of incentive bonuses in the medical organization, by the example of the structure containing a health center. Prepared algorithm of individual incentive bonuses presents the requirements for formulating criteria, and a form of the final protocol, painted traffic scheme documents is developed.